Faktor Yang Mempengaruhi Tingkat Stres Orang Tua Pada Berat Badan Lahir Rendah (BBLR) Yang Di Rawat Di Unit Perawatan Intensif Neonatus RSUD DR. Moewardi Di Surakarta - Sunarsih Rahayu; Insani Apriliana Nurhayati (Poltekkes Kemenkes Surakarta, 2016)
Abstract : Stress Level, Low Birth Weight (LBW), Parents, Intensive Neonatal Care Unit. Treatment of LBW baby in intensive room has impact for parents such as: fear, guilty, stress and anxiety. Stres feeling for parents may not be ignored because, if feel stress, it makes parents can not care to the baby well. Objectives of the study was to know the factors which influence stress level of parents (ignorance of caring baby, less support system, coping mechanism and less communication among family) on LBW which is treated in Intensive Neonatal Care Unit at Dr. Moewardi Hospital. This type of research was analytic descriptive, cross sectional approachment at 30 parents LBW baby which is treated in Intensive Neonatal Care Unit at Dr. Moewardi Hospital on January-April 2016. Sampling technique uses total sampling. Inklusi criteria of LBW parents in Intensive Neonatal Care Unit who become respondent. Eklusi criteria of LBW parents who has mental disorders and sick when they are give questionnaire. The level of stress is measured by using Deppresion Anxiety Stress Scale (DASS-42) and the factors which influence stress level (parents knowledge, coping mechanism and less communicaton among the family) used questionnaire in closed ended form. Analysis data used Lamda. Results was show that Ignorence of caring baby (p=0,022), less support system (p=0,044), and less communication among the family (p=0,010) effected to stress level. While, coping mechanism (p=0,056) does not effected to stress level.Conclusion, Less support system, ignorance of caring baby and less communication among the family related with stress level.